2015
DOI: 10.5152/tjg.2015.0090
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine versus lidocaine plus benzydamine as a topical anesthesia regimen for unsedated upper gastrointestinal endoscopy: A comparison study

Abstract: Background/Aims: The aim was to assess the efficacy of adding benzydamine (B) spray to standard treatment with a lidocaine (L) spray before upper gastrointestinal endoscopy (UGE) as a topical anaesthetic regimen. Materials and Methods: A total of 118 adult patients undergoing outpatient UGE were randomly assigned to receive L (n=44), LB (n=38) or B (n=36) before the procedure. The primary outcome was the patient tolerance score, which represents a summative evaluation of the taste of the anesthetic agent, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…This was not done because the percentage of patients with severe discomfort was very low. Third, lidocaine was used for topical anesthesia in this study because lidocaine is commonly used in clinical practice, while previous studies also compared other medications for topical anesthesia 20 22 , which may be further assessed in future.…”
Section: Discussionmentioning
confidence: 99%
“…This was not done because the percentage of patients with severe discomfort was very low. Third, lidocaine was used for topical anesthesia in this study because lidocaine is commonly used in clinical practice, while previous studies also compared other medications for topical anesthesia 20 22 , which may be further assessed in future.…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that there is less increase in oral secretion in the LS group (9.3%) compared to the DS group (51.7%), compatible with the literature ( p =0.038). In a study done in our country comparing sore throat, sore throat was observed the least in the lidocaine benzydamine group in the comparison of lidocaine spray, lidocaine benzydamine spray and benzydamine spray, while it was observed the most in the benzydamine group [18]. In our study, sore throat was observed to a significantly lesser degree in the LS group (3.7%) compared to the DS group (35.6%) compatible with the literature ( p =0.019).…”
Section: Discussionmentioning
confidence: 99%
“…[10] This procedure can be irritating for patients in case of not using sedatives due to gag reflex stimulation. [2] UGE without using sedatives has some advantages including lower incidence of cardiopulmonary complications, shorter duration of procedure, fewer costs, and patients’ ability of controlling self-care after endoscopy. [1112] On the other hand, sedation can cause better tolerance and less irritation for patients.…”
Section: Discussionmentioning
confidence: 99%
“…as well regarding patients’ tolerance while spray plus benzydamine was accompanied with less sore throat and easier esophageal intubation. [2] It should be noted that less sore throat may have occurred because of local anti-inflammatory effect of benzydamine regardless of lidocaine spray.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation